{4-[(2,4-Dichlorobenzoyloxy)methyl]-1-phenyl-1H-1,2,3-triazol-5-yl}methyl 2,4-dichlorobenzoate - Ismatov, Dilmurot (International Union of Crystallography, 2011)
In the title molecule, C(24)H(15)Cl(4)N(3)O(4), the triazole ring makes dihedral angles of 72.02 (12), 81.60 (12) and 73.82 (11)°, respectively, with the adjacent phenyl ring and the two dichlorobenzene rings. In the crystal, a weak C—H⋯N interaction, a short Cl⋯Cl contact [3.307 (2) Å] and a π–π stacking interaction [centroid–centroid distance = 3.568 (4) Å] are observed. An intramolecular C—H⋯O interaction is also present.